PELAKSANAAN PEMBELAJARAN TATAP MUKA TERBATAS DI KELOMPOK BERMAIN AL-LUBAWI SALATIGA - Ibdaul Latifah; Sri Murniyati (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2022)
This study aims to describe the implementation of face-to-face learning in the Al Lubawi playgroup Salatiga. This type of research is descriptive qualitative with data collection techniques in the form of interviews, observations and documentation. Sources of data used in this study are primary and secondary data sources. Primary data researchers obtained from interviews with principals, teachers and parents of students. While secondary data obtained from documentation and school archives. The results showed that the implementation of face-to-face learning was limited to running smoothly even though there were some problems. Preparations for conducting limited face-to-face meetings have been carried out by the school including filling out a limited PTM checklist and all educators and teaching staff have vaccinated. The implementation is carried out with very strict procedures and still adheres to health protocols. limiting the number of children in one classroom to only 5 students and reducing the time allocation for only 1 hour. Problems that arise in the limited face-to-face implementation are children who do not fully comply with health protocols, the habits of children who are not disciplined in dealing with school and the shortened time allocation causes the material provision is not optimal.